(untitled) (Anwer Khan Modern Medical College Journal, 2017)
Background: Morphine is an opioid analgesic which is used to treat moderate to severe pain but has a number of side effects. This study is aimed to explore that combination of morphine and a-tocopherol (aT) are better analgesic as well as anti-inflammatory effect than that of morphine alone. Objective: To assess the effects of combination of morphine with a-tocopherol on pain and inflammation. Methods: This prospective experimental study was conducted in the Department of Physiology, Bangabandhu Sheikh Mujib Medical University (BSMMU), Shahbag, Dhaka from January 2013 to December 2013. For this purpose, 15 male Long Evans rats were studied. On the basis of vitamin and drug administrations, the rats were divided into three (3) groups (5 rats in each). Control group received normal saline, one experimental group received morphine sulphate (MS) at a dose of 3 mg/kg body weight and another experimental group received combination of MS with aT at a dose of 3 mg/kg body weight and 500 mg/kg body weight, respectively. All the groups received single dose and equal volume (1 ml) through intraperitoneal route 1 hour before the test. Just one hour after administrations, they were subjected to formalin test followed by formalin induced paw edema test. The data were statistically analyzed by ANOVA followed by Bonferroni Post Hoc test. Results: Combined administration of MS and aT lowered the variables for nociceptive pain, central analgesic activity, inflammatory pain as well as inflammation than individual administration of MS. Conclusion: From this study it may be concluded that combined administration of morphine sulphate and atocopherol were more effective in lowering pain and inflammation than individual administration of morphine. Anwer Khan Modern Medical College Journal Vol. 8, No. 1: Jan 2017, P 24-29